Whey block freeze concentration aiming a functional fermented lactic beverage with the addition of probiotic and guabiroba pulp (Campomanesia xanthocarpa O. Berg), a native Brazilian fruit - PRESTES, Amanda Alves; SILVEIRA, Matheus Fermino; CANELLA, Maria Helena Machado; HELM, Cristiane Vieira; ANDRADE, Dayanne Regina Mendes; FERREIRA, Ana Letícia Andrade; AMBONI, Renata Dias de Melo Castanho; FEDRIGO, Isabela Maia Toaldo; HERNÁNDEZ, Eduard; PRUDENCIO, Elane Schwinden (Food Science and Technology, 2023)
The scientific importance involved in this study was the use of whey, a co-product of the cheese industry, and its performance during the freeze concentration process. Moreover, the best-concentrated whey from the freeze concentration process, about the total solids, proteins, and mineral contents, was used to prepare two functional fermented lactic beverages. Therefore, whey was subjected to the freeze concentration in blocks with gravitational thawing. Process performance indicated better yields and efficiency for the second stage of freeze concentration. Concentrated whey 2 was used to prepare two fermented lactic beverages added with probiotics: one without adding guabiroba pulp (control) and a beverage incorporated with 10% guabiroba pulp. Containing guabiroba pulp was not enough to modify the total solids, proteins, and mineral contents. However, it decreased pH values, changed the color to an orange hue, and decreased luminosity. The fermented lactic beverage added with probiotic and 10% guabiroba pulp showed 1.61× more phenolic compounds and an increase of 164% for each evaluated carotenoid content compared with the control beverage.